2022
DOI: 10.3390/biomedicines10071754
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase in the Perivascular Adipose Tissue

Abstract: Perivascular adipose tissue (PVAT) is a special type of ectopic fat depot that adheres to most vasculatures. PVAT has been shown to exert anticontractile effects on the blood vessels and confers protective effects against metabolic and cardiovascular diseases. PVAT plays a critical role in vascular homeostasis via secreting adipokine, hormones, and growth factors. Endothelial nitric oxide synthase (eNOS; also known as NOS3 or NOSIII) is well-known for its role in the generation of vasoprotective nitric oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 140 publications
0
22
0
Order By: Relevance
“…Introduced as unexpected evidence in adult humans in 2007 [ 61 ], the vasoprotective action of perivascular adipose tissue (PVAT) has been rediscovered as crucial in controlling vascular function in the presence and absence of a pathological condition [ 62 , 63 , 64 , 65 ]. Studies investigating the protective or damaging effect of perivascular adipose tissue are shown in Table 2 [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduced as unexpected evidence in adult humans in 2007 [ 61 ], the vasoprotective action of perivascular adipose tissue (PVAT) has been rediscovered as crucial in controlling vascular function in the presence and absence of a pathological condition [ 62 , 63 , 64 , 65 ]. Studies investigating the protective or damaging effect of perivascular adipose tissue are shown in Table 2 [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PVAT eNOS has been shown to exert an important function that is included in the protective role of PVAT. Recently, Man et al demonstrated that, in the presence of obesity-related metabolic diseases, PVAT eNOS may be even more important than the share of endothelial eNOS in promoting obesity-induced vascular dysfunction, which can ultimately be attributed to certain specific functions of PVAT eNOS [ 65 ]. Finally, in a third report, it was suggested that obesity-induced loss of the anti-contractile effect of PVAT was reversed after calorie restriction in a mouse model [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…eNOS expression has been identified in thoracic PVAT. Of note, any cardiovascular risk factors that lower availability of l -arginine and BH 4 promote eNOS uncoupling and therefore superoxide production [ 7 ]. Consequently, the overproduced ROS by PVAT during pathological conditions cause oxidative damage to adjacent vascular cells.…”
Section: Pvat and Vascular Cellsmentioning
confidence: 99%
“…Ucp-1 ), presence of numerous lipid droplets, and high mitochondrial content [ 6 ]. Besides, certain PVAT, predominantly mesenteric PVAT, is more-white adipose tissue (WAT)-like, due to lower expression of thermogenic genes like UCP-1, presence of larger lipid droplets, and low mitochondrial number [ 7 ]. Meanwhile, certain PVAT, like coronary PVAT, is more beige adipose tissue (BeAT)-like because some brown adipocyte-associated genes, such as UCP-1 and carnitine palmitoyltransferase 1B, are differentially expressed when compared to those of BAT [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Huige’s group and our group found that an HFHSD with insulin resistance induced minimal endothelial dysfunction in mouse aortas [ 5 ]. Huige revealed that an HFHSD impaired endothelial dysfunction in the aortas with perivascular adipose tissue (PVAT) due to eNOS uncoupling in PVAT [ 11 , 12 ]. We hypothesized that in an HFHSD, the perivascular component alone is impaired, and the additional factors impair not only PVAT but also the vessels themselves.…”
Section: Introductionmentioning
confidence: 99%